Complying winery marketing strategies based on attitudes and perceptions towards winery terroir - Spyridon Mamalis; Irene (Eirini) Kamenidou; Aikaterini Karampatea; Spyridon Arseniou; Elisavet Bouloumpasi; Adriana Skendi; Glykeria Fourkioti (Journal of Tourism, Heritage & Services Marketing, 2024)
Purpose: This study explores winery visitors' attitudes towards terroir significance as well as perceptions of terroir for marketing communication and as a competitive advantage for wineries, and uses these as a basis to examine intergenerational cohort differences.